Quality of Life and Sexual Functioning After Vulvar Reconstruction With the Lotus Petal Flap. Issue 9 (November 2018) - Hellinga, Joke; te Grootenhuis, Nienke C.; Werker, Paul M.N.; de Bock, Geertruida H.; van der Zee, Ate G.J.; Oonk, Maaike H.M.; Stenekes, Martin W.
Abstract : Objective: Resection of (pre) malignant lesions in the vulvoperineal area may result in large defects that cannot be closed primarily. The lotus petal flap technique is widely used for reconstruction. The aim of this study was to evaluate both quality of life (QoL) and sexual functioning of patients who underwent the lotus petal flap procedure, because no data are available on this topic. Methods: A cross-sectional study was performed on all eligible patients (N = 38) who underwent the lotus petal flap procedure between 2005 and 2016. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30, Female Sexual Function Index, and Body Image Scale were used to evaluate QoL and sexual functioning. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30 and Female Sexual Function Index scores were compared with scores of age-matched healthy women. Results: Twenty-six patients (68%) responded. The mean (SD) age was 65.5 (16.3) years, and the median follow-up time was 38.5 months (range 16–141 months). Quality of life scores were lower compared with healthy women in the domains physical, role, and social functioning. Sexual activity rates were comparable with healthy women; however, sexual functioning was worse. Although patients were satisfied about their sexual life, pain was reported. Conclusions: Patients who underwent vulvar reconstructive surgery with lotus petal flaps seem to have a lower QoL compared with healthy women. Patients report more pain during sexual activity but are satisfied about their sexual functioning. These results should be included in preoperative counseling and follow-up of future patients eligible for vulvar reconstruction with a lotus petal flap. Abstract : Supplemental digital content is available in the text.